The Opioid Crisis and Federal Criminal Prosecution. Issue 2 (June 2018) - Rothberg, Rachel L.; Stith, Kate
This article examines how federal law enforcement has responded to the opioid epidemic nationally and in a variety of locales. We focus in depth on two initiatives, including prosecution in opioid-death cases, undertaken by the U.S. Attorney's Office in Connecticut.